Branchial fistula: review of literature and case report - Mahajan, Salil; Sorout, Jaya (International Surgery Journal, 2017)
The branchial arches are the embryological precursors of the face, neck and pharynx. Second most common congenital lesions of the head and neck in children are the anomalies of the branchial arches, with second arch anomalies by far the most common. Clinically, these congenital anomalies may present as cysts, sinus tracts, fistulae or cartilaginous remnants with typical clinical and radiological findings. We report the case of 11-month-old male child with congenital Type I Second branchial fistula on the left side of neck.